Pengaruh PENGARUH BUDAYA LITERASI TERHADAP PROFESIONALISME GURU: STUDI KASUS PADA SEKOLAH MENENGAH PERTAMA NEGERI DI KOTA MAKASSAR - Irsan Kadir; Roslyn Roslyn; Surya Dharma (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The purpose of this research is to decide 1) the description of teacher literacy culture at Makassar CityState Junior High Schools, 2) the description of teacher professionalism at Makassar City State JuniorHigh Schools, and 3) the impact of teacher literacy culture on teacher professionalism at Makassar CityState Junior High Schools. Makassar. The population of this research consisted of all civil servant teachersat SMP Negeri in Makassar, a total of 995 teachers. The slovin formula was used to obtain convenientsampling method using simple random sampling with a minimum sample of 91 government junior highschool teachers in Makassar. The data was collected using a Likeart scale questionnaire, which first testedthe instrument's validity using the Gregory model for internal validity, Pearson's product moment forempirical validity, and Cronbach's alpha for reliability testing. Descriptive statistics and simple linearregression statistics were used to analyze the data. The study's findings show that 1) the description ofteacher literacy culture is generally in the high category, 2) The description of teacher professionalism isgenerally positive. 3) There is a positive and significant influence of literacy culture on teacherprofessionalism at public junior high schools in Makassar, with the a 20% effect.